Microbiota-Immune Interaction Landscape of Treg/Th17 Dynamic Balance in Regulating Mucosal Immune Homeostasis: From Molecular Switches to Precision Intervention in Inflammatory Bowel Disease - Jing Wang; Mengwei Sun; Baoqing Zhang (Discovery Medicine, 2026)
Mucosal inflammatory disorders, including inflammatory bowel disease (IBD), have increased steadily in prevalence worldwide. These conditions follow a protracted clinical course with high complication rates and no curative therapies. The breakdown of intestinal mucosal immune homeostasis is central to their pathogenesis. Among the key regulatory pathways, the balance between regulatory T cells (Tregs) and T helper 17 (Th17) cells is a pivotal determinant of mucosal immune tolerance and the containment of excessive inflammatory responses. This review synthesizes current knowledge on the biological characteristics, differentiation regulatory networks, and functional crosstalk between Tregs and Th17 cells. We describe how the mutual antagonism between the lineage-specific transcription factors Forkhead box P3 (Foxp3) and retinoic acid-related orphan receptor gamma t (RORγt) acts as a core molecular switch governing this balance, while T cell receptor (TCR) signaling, the cytokine microenvironment, and epigenetic modifications form its upstream regulatory network. We further discuss the precise mechanisms by which commensal microbiota and their metabolites, intestinal epithelial barrier integrity, and regional heterogeneity of mucosal tissues modulate the Treg/Th17 balance, and we dissect how disruption of this balance drives IBD onset and progression. We also summarize Treg/Th17-related biomarkers for IBD diagnosis and disease monitoring and emerging therapeutic strategies targeting this balance. Finally, we outline priority research directions, emphasizing the translational potential of single-cell multi-omics and spatial transcriptomics for achieving tissue-specific precision regulation of Treg/Th17 balance in IBD.